THE POLITICAL IDEOLOGY AND PHILOSOPHY OF BANGABANDHU SHEIKH MUJIBUR RAHMAN IN THE CONTEXT OF FOUNDING A NATION - Shah Mohammad Omer Faruqe Jubaer; Muhammed Nyeem Hassan (Scholar Express Journal, 2021)
Bangabandhu Sheikh Mujibur Rahman is regarded as a "liberation emblem." He was a one-of-a-kind nationalist leader who freed the people of East Pakistan (now Bangladesh) from West Pakistan's oppression. Sheikh Mujibur Rahman has played a pivotal role in the Bangladeshi independence movement. He has been dubbed "Father of the Nation" due to his dominating role and presence. Sheikh Mujibur Rahman is the most towering figure in Bangladeshi politics has been explained, claimed, and counterclaimed by political parties and intellectuals as a secular, a Bengali, and a socialist or a mix of all. As a leader, there is no end to his merits and there is no end to writing about him. There is very little scholastic research on the ideology and political philosophy of Sheikh Mujibur Rahman, so the Primary object of this Research Paper is to identify and clarify the concept regarding the philosophy and ideology of Sheikh Mujibur Rahman which reflects the guiding principles of The Constitution of the People ’s Republic of Bangladesh
Keywords: Political Ideology; Political Philosophy; Sheikh Mujibur Rahman; Political Philosophy of Bangabandhu Sheikh Mujibur Rahman